2011
DOI: 10.1002/chem.201002589
|View full text |Cite
|
Sign up to set email alerts
|

Desilication Mechanism Revisited: Highly Mesoporous All‐Silica Zeolites Enabled Through Pore‐Directing Agents

Abstract: The role of pore-directing agents (PDAs) in the introduction of hierarchical porosity in silicalite-1 in alkaline medium was investigated. By incorporation of various PDAs in aqueous NaOH, homogenously distributed mesopores were introduced in 2.5 μm silicalite-1 crystals. It was proven for the first time that framework aluminum is not a prerequisite for the introduction of intracrystalline mesoporosity by desilication. The pore-directing role is not directly exerted by framework trivalent cations metals, but b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
249
2
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 251 publications
(266 citation statements)
references
References 52 publications
12
249
2
3
Order By: Relevance
“…20 and 50. 35,98,99 However, it has recently been shown that the partial coverage of the outer crystal surface with organic molecules allows the controlled desilication even of aluminium-free zeolites, 98 while a combined acid-base treatment allows the desilication even of Al-rich zeolites. 100,101…”
Section: Demetalationmentioning
confidence: 99%
“…20 and 50. 35,98,99 However, it has recently been shown that the partial coverage of the outer crystal surface with organic molecules allows the controlled desilication even of aluminium-free zeolites, 98 while a combined acid-base treatment allows the desilication even of Al-rich zeolites. 100,101…”
Section: Demetalationmentioning
confidence: 99%
“…Alkaline leaching, performed in aqueous NaOH and tetraalkylammonium hydroxides mixtures, leads to the dissolution of both Si and smaller amounts of Al species from the framework. Nevertheless, most of these extracted Al species are able to realuminate on the mesopore surface, resulting in the lowering the Si/Al ratio of the hierarchical [9,10]. Zeolite desilication has been successfully applied to produce a large number of hierarchically structured zeolites MFI [11,12]MTW [13], MOR [14,15], FER [16,17], FAU [18], and Beta [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the Tmax of the Brønsted acid of HZ-DA (412 °C) was higher than those of HZ and HZ-D, and a slight increase of the Brønsted site concentration from 0.14 to 0.15 mmol/g was found. This small increase ascertains that small amounts of extracted Al species from the ZSM-5 matrix can be reincorporated into the framework [26]. Figure 6 shows the NH 3 -TPD profiles, and Table 2 lists the acid site densities.…”
Section: Resultsmentioning
confidence: 78%
“…As for HZ-DA, Al(Td) seemed to grow back from 77% to 87% with Al(Oh) that decreased from 23% to 13%. The increased Al(Td) ratio was possible caused by a re-alumination process through which some extra-framework Al could be reinserted into the ZSM-5 framework in an acidic environment [25,26], while the decrease of Al(Oh) indicates that some extra-framework Al species were removed from the outer surface. Briefly, HZ-D had the highest compositions of Al(Oh) and the lowest compositions of Al(Td) among tested catalysts.…”
Section: Introductionmentioning
confidence: 99%